2010
DOI: 10.1093/bja/aeq018
|View full text |Cite
|
Sign up to set email alerts
|

Influence of steep Trendelenburg position and CO2 pneumoperitoneum on cardiovascular, cerebrovascular, and respiratory homeostasis during robotic prostatectomy

Abstract: Background. The steep (408) Trendelenburg position optimizes surgical exposure during robotic prostatectomy. The goal of the current study was to investigate the combined effect of this position and CO 2 pneumoperitoneum on cardiovascular, cerebrovascular, and respiratory homeostasis during these procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

14
133
4
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(165 citation statements)
references
References 16 publications
(10 reference statements)
14
133
4
4
Order By: Relevance
“…Carbon dioxide pneumoperitoneum combined with an acute Trendelenburg position for several hours has been reported to be well tolerated by patients, and it has been suggested that this is because it increases cerebral tissue oxygen saturation slightly and maintains CPP within the autoregulated range [8,9]. In addition, in another earlier study, a slight increase in rSO 2 occurred after the institution of carbon dioxide pneumoperitoneum in a steep Trendelenburg position, which suggests that cerebral ischaemia might not occur during this procedure [6].…”
Section: Discussionmentioning
confidence: 92%
“…Carbon dioxide pneumoperitoneum combined with an acute Trendelenburg position for several hours has been reported to be well tolerated by patients, and it has been suggested that this is because it increases cerebral tissue oxygen saturation slightly and maintains CPP within the autoregulated range [8,9]. In addition, in another earlier study, a slight increase in rSO 2 occurred after the institution of carbon dioxide pneumoperitoneum in a steep Trendelenburg position, which suggests that cerebral ischaemia might not occur during this procedure [6].…”
Section: Discussionmentioning
confidence: 92%
“…The increase in dead space can lead to an increase in arterial-alveolar gradient for CO 2 . The study by Kalmar et al [24] found that the end-tidal CO 2 (ETCO 2 ) measurement can be around 1.41 kPa lower than arterial pCO 2 after 2 hours in the Trendelenburg position. Tidal volumes and respiratory rate need to be increased to prevent hypercarbia and respiratory acidosis.…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult to accurately monitor urine output and blood loss in these patients because suction from the abdomen will contain a variable mixture of blood, urine and wash. Not all fluid will be evacuated into the suction bowls. Regular HemaCue measurements are useful if excessive blood loss is suspected [24]. Renal perfusion decreases due to a combination of raised intra-abdominal pressure and activation of the renin, aldosterone and angiotensin systems.…”
Section: Discussionmentioning
confidence: 99%
“…Whether or not these physiologic changes can lead to cardiovascular or neurologic injury in elderly patients undergoing long robotic-assisted MIS procedures has not been well established. However, more recently, it was found that prolonged steep Trendelenburg and pneumoperitoneum was tolerated well and that regional cerebral oxygenation was preserved in male patients undergoing Robotic-assisted laparoscopic radical prostatectomies [20]. Other risks of steep Trendelenburg also involve possible injury to the eye, even blindness, as intraocular pressures are elevated for long durations of robotic-assisted MIS [21] [22].…”
Section: Discussionmentioning
confidence: 99%